Effectiveness of Dietary Interventions in Reducing Childhood Obesity Among Primary School Children in Bangladesh (Eastern Medical College Journal, 2026)
Background: Childhood obesity is becoming a significant health issue in Bangladesh, with dietary factors playing a major role in its rise among schoolchildren. This study aimed to assess the impact of dietary habits on the prevalence of childhood obesity in primary school children in Bangladesh.Materials and Methods: This cross-sectional study was conducted with 300 primary school children aged 6 to 12 years selected from urban and rural schools. A purposive sampling was applied to take the sample. Dietary patterns, sociodemographic factors, and obesity status were assessed. SPSS version 26 was used for data analysis.Results: Among the 300 children, 33.3% were classified as obese. Of the obese children, 80% consumed high-calorie foods regularly, and 70% frequently drank sugary beverages. Parental education level was significantly associated with obesity risk, with an odds ratio (OR) of 1.8.Conclusion: The findings highlight the critical role of dietary habits and socio-economic factors, such as parental education, in childhood obesity. Interventions targeting improved dietary behaviors and addressing socio-economic disparities are essential to combat obesity in Bangladesh.Eastern Med Coll J. July 2025; 10 (2): 89-94